Rethinking the Bribri Language Subject from the Curricular Design of Second Languages - Serrato Pineda, Luis (2023)
This paper proposes and exemplifies, specifically, how the program of the Bribri Language subject could be redesigned from the theoretical-methodological framework of the curricular design of second languages. To achieve this, first, general principles of the curricular design of second languages are exposed; then, it is presented and discussed how these could be applied in an eventual process of curricular (re)design of the referred subject. The conclusion is that, by contemplating linguistic, sociocultural, and pedagogical elements, the curricular design of second languages offers a comprehensive conceptual framework that could yield positive results in the formal teaching of the Bribri language.